Capillary electrophoresis in association with chemometrics approach for bitterness hop (Humulus lupulus L.) classification. Issue 11 (25th March 2018) - Duarte, Lucas Mattos; Adriano, Luiz Henrique Cantarino; de Oliveira, Marcone Augusto Leal
Abstract: The precursor compounds related to the bitterness of beer are called α‐acids. These compounds are extracted from the hop, which is an important ingredient in the brewing process. These compounds were analyzed by capillary electrophoresis. The electrophoretic method used 160 mmol/L of ammonium carbonate (pH 9) as BGE (background electrolyte), a voltage of +20 kV in a capillary with 50 μm of internal diameter and with a 62.5 cm of total length (54 cm effective). The samples were injected in hydrodynamic mode applying a pressure of 25 mbar for 5 s and the analytes were detected at 230 nm. A hydromethanolic extraction during 3 h was considered as the optimum condition for the sample preparation using MeOH/H2 O 80:20 v/v as the extract solution. From the optimized conditions the electropherograms were evaluated for their use as input for chemometric modeling. Preprocessing investigation for electrophoretic data taking into account the alignment, denoising and baseline correction, and variable selection were considered before the chemometric modeling using principal component analysis (PCA). The electrophoretic data were systematically evaluated to find the optimum conditions to modeling. A PCA analysis for all tests was carried out using different preprocessing methods and, an explained variance higher than 90% was achieved in all of them. The optimized chemometric method worked with aligned and meancentered data. From this approach, a simple and efficient method to classify hop samples with high and low α‐acids content without the use of analytical standards was established from a simple electrophoretic analysis.